Evaluation of the Antibacterial Effects of Single and Combined use of Different Irrigation Solutions Against Intracanal Enterococcus Faecalis - Hatice Buyukozer Ozkan; Funda Kont Cobankara; Zafer Sayin; Fusun Ozer (University of Zagreb. School of Dental Medicine, 2020)
Objectives: This study assessed the antibacterial activity of both separate and combined uses of 5.25% sodium hypochlorite (NaOCl), 2% chlorhexidine (CHX), 17% ethylenediaminetetraacetic acid (EDTA), 3% hydrogen peroxide (H2O2), MTAD, SmearClear (SC) and 13.8% chlorine dioxide (ClO2) irrigation solutions against Enterococcus faecalis. Material and Methods: Two hundred eighty single rooted human premolars were randomly grouped into 26 test and 2 control (negative and positive) groups and were incubated for 24 h with E. faecalis, except for the negative control group. The tested solutions were as follow: NaOCl; CHX; ClO2; MTAD; SC; EDTA; H2O2; NaOCl + CHX; NaOCl + MTAD; SC + NaOCl; EDTA + NaOCl; H2O2 + NaOCl; ClO2 + CHX; CHX + MTAD; SC + CHX; EDTA + CHX; CHX + H2O2; ClO2 + MTAD; SC + ClO2; EDTA + ClO2; ClO2 + H2O2; SC+MTAD; EDTA+MTAD; MTAD + H2O2; SC + H2O2; and EDTA + H2O2. Optic density values were recorded at 0, 6, 12, 18, 24, 30, 36, 42 and 48 h and bac-terial growth curve created for each solution. Results: The CHX, MTAD and ClO2 showed a high poten-tial for the elimination of E. faecalis, both alone and in all combinations. The EDTA, H2O2, H2O2 + EDTA, H2O2 + NaOCl and SC + NaOCl groups showed less antibacterial activity than the other groups. The SC + CHX group showed the best antibacterial effect against E. faecalis. Conclusion: The SC + CHX com-bination can be recommended as the most effective irrigation regimen against E. faecalisin persis-tent endodontic infections.